Care seeking and attitudes towards treatment compliance by newly enrolled tuberculosis patients in the district treatment programme in rural western Kenya: a qualitative study - Mchembere Walter; Agaya Janet A; van't Hoog Anna H; Ayisi John G; Nyamthimba Peter O; Muhenje Odylia; Marston Barbara J (BMC, 2011)
Abstract Background The two issues mostly affecting the success of tuberculosis (TB) control programmes are delay in presentation and non-adherence to treatment. It is important to understand the factors that contribute to these issues, particularly in resource limited settings, where rates of tuberculosis are high. The objective of this study is to assess health-seeking behaviour and health care experiences among persons with pulmonary tuberculosis, and identify the reasons patients might not complete their treatment. Methods We performed qualitative one-on-one in-depth interviews with pulmonary tuberculosis patients in nine health facilities in rural western Kenya. Thirty-one patients, 18 women and 13 men, participated in the study. All reside in an area of western Kenya with a Health and Demographic Surveillance System (HDSS). They had attended treatment for up to 4 weeks on scheduled TB clinic days in September and October 2005. The nine sites all provide diagnostic and treatment services. Eight of the facilities were public (3 hospitals and 5 health centres) and one was a mission health centre. Results Most patients initially self-treated with herbal remedies or drugs purchased from kiosks or pharmacies before seeking professional care. The reported time from initial symptoms to TB diagnosis ranged from 3 weeks to 9 years. Misinterpretation of early symptoms and financial constraints were the most common reasons reported for the delay. We also explored potential reasons that patients might discontinue their treatment before completing it. Reasons included being unaware of the duration of TB treatment, stopping treatment once symptoms subsided, and lack of family support. Conclusions This qualitative study highlighted important challenges to TB control in rural western Kenya, and provided useful information that was further validated in a quantitative study in the same area.